Kryteria i tryb formułowania oceny administracji rządowej przez sejmik samorządowy (na przykładzie woj. wrocławskiego) - Kieres, Leon (Wydział Prawa i Administracji UAM, 1991)
The purpose of the article is to determine the criteria of evaluation of the activity of government administration in a province. Such an evaluation is formulated by the Self-Government Parliament. The author analyses the legislation that may pertain to the said evaluation and indicates that in principle the legislator has not defined those criteria. Also the procedure of formulating the evaluation has been left outside the scope of law. The author describes the procedure adopted by one of the provincial Parliaments. He indicates that a necessary element of such procedure is the participation of communes, and offers remarks on the way in which the participation of communes may be realized. Finally, the author puts forth proposals to improve the activity of government administration, taking into account both the interests of territorial self-government as well as the interests of the state.
Criteria and procedure of formulating the evolution of government administration by self-government diet